Providing a Prostate Cancer Detection and Prevention Method With Developed Deep Learning Approach - Alireza Zarei; Elias Mazrooei Rad; Shahryar Salmani Bajestani; Seyyed Ali Zendehbad (Prostate Cancer)
Conclusions: The simulation results indicated that the proposed method has a performance advantage over the other state-of-the-art methods, and the accuracy of this method is up to 97.41%.